(untitled) (The Review of Diabetic Studies, 2024)
Background Inadvertent perioperative hypothermia (IPH), defined as a core body temperature below 36°C, remains one of the most pervasive complications in modern surgical practice, affecting a significant proportion of patients undergoing general and neuraxial anesthesia. While historically viewed as a benign side effect of anesthesia, IPH has been implicated in a cascade of adverse physiological outcomes, including coagulopathy, prolonged drug metabolism, and myocardial ischemia. Most critically, its association with surgical site infections (SSIs) has been a subject of intense investigation and debate. Theoretical models suggest that hypothermia-induced vasoconstriction impairs neutrophil function and oxidative killing, thereby increasing susceptibility to bacterial colonization. However, the translation of this physiological mechanism into clinical infection rates varies across surgical populations and eras of practice. Objectives This systematic review aims to comprehensively evaluate the current evidence regarding the impact of intraoperative hypothermia on SSI rates across diverse surgical specialties. Furthermore, it seeks to critically assess the efficacy of nurse-led warming interventions—specifically comparing active versus passive modalities—and to identify the barriers and facilitators influencing the implementation of evidence-based thermal management protocols in the perioperative setting. Methods A systematic search of major medical databases (PubMed, Embase, CINAHL, Cochrane Library) was conducted to identify randomized controlled trials (RCTs), systematic reviews, and high-quality observational studies published through 2023. The review adhered to PRISMA guidelines. Data synthesis focused on the correlation between thermal endpoints and infection outcomes, the comparative effectiveness of warming technologies (e.g., forced-air warming vs. resistive heating), and the implementation science of thermal care bundles. Results The review synthesized data from over 28,000 patients. While foundational studies from the 1990s demonstrated a threefold increase in SSI risk with mild hypothermia, contemporary meta-analyses (2020–2023) reveal a more nuanced landscape. Aggregate data often show no statistically significant association between hypothermia and SSI in the general surgical population, likely due to improved baseline standards of care. However, significant risk elevations persist in specific subgroups, notably breast surgery (OR 1.97) and patients experiencing core temperatures below 35°C (OR 2.12). Regarding interventions, active forced-air warming (FAW) remains the most effective method for maintaining normothermia, particularly when combined with a prewarming protocol of at least 30 minutes. The safety of FAW in orthopedic implant surgery remains debated but generally supported by regulatory bodies. Conclusion Maintenance of normothermia represents a critical, modifiable factor in surgical safety. While the "universal" link to SSI has weakened with modern surgical advances, hypothermia remains a potent risk factor for vulnerable subgroups. Perioperative nursing interventions, particularly the consistent application of active prewarming and intraoperative warming, are essential. Future practice must focus on overcoming implementation barriers through the adoption of standardized thermal care bundles.